Assembly and characterization of the complete mitogenome of Bauhinia purpurea (Leguminosae) - Siqi Xie; Yong Chen; Danjing Zheng; Shukai Luo; Shiyuan Meng; Yan Zhong (BMC Genomic Data)
Abstract Objective Mitochondrial genome sequences are very useful for understanding the mitogenome evolution itself and reconstructing phylogeny of different plant lineages. Bauhinia purpurea, a species from the legume family Leguminosae, is widely distributed in South China and has high ornamental value. Here, we sequenced and assembled the mitogenome of B. purpurea to provide a useful genetic resource for further evolutionary studies. Data description We assembled and characterized the complete mitogenome of B. purpurea based on Illumina sequence data. The mitogenome size was 525,727 bp, and its GC content was 45.38%. A total of 35 protein-coding genes, 16 tRNA genes, and 3 rRNA genes were identified in the mitogenome. We also identified 124 pairs of repeats and 6 mitogenome sequences of plastid origin (MTPTs). These MTPTs range from 108 bp to 751 bp, covering 0.65% of the mitogenome.